ANALISIS KEMAMPUAN BERPIKIR KRITIS SISWA DALAM MENYELESAIKAN SOAL HOTS DITINJAU DARI KEAKTIFAN PADA PEMBELAJARAN COOL-CRITICAL-CREATIVE-MEANINGFUL - Aini, Afifah Nur; Putri, Intan Safila (Math Educa Journal, 2023)
Critical thinking is one of the characteristics of higher-order thinking skills (HOTS). Indikators of critical thinking skills include interpretation, inference, analysis, and evaluation. One alternatif to optimize students' thinking skills is through cool-critical-creative-meaningful (3CM) learning. This research is a pre-experimental descriptive type with a one-shot case study design. The instruments used were lesson plans, guidelines for observing student activity, HOTS-type critical thinking skills tests, and interview guidelines. The research subjects were 33 students in class VIII A of SMP Plus Darus Sholah Jember. The research procedure begins with 3CM learning in the subject class. During the learning process, student activity was observed and classified into low, medium, and high categories. Then 2 subjects were selected for each category to take the critical thinking ability test. The results of the data analysis show that students who are more active in learning 3CM show better critical thinking skills. This is because active learning can be a supporting factor for students critical thinking skills.